Central Venous Catheterization in the ICU: A Comparison of Anatomical Landmark and Ultrasound-Guided Techniques - Pratiaksa, Ardian; Purwoko; Muhammad Husni Thamrin; Bambang Novianto Putro; Fitri Hapsari Dewi (Journal of Anesthesiology and Clinical Research, 2025)
Introduction: Central venous catheterization (CVC) is frequently required in intensive care units (ICUs) for administering medications, fluids, and monitoring central venous pressure. However, CVC insertion can lead to complications such as arterial puncture, hematoma formation, and pneumothorax. Ultrasound guidance has been advocated to reduce these complications, but its effectiveness in the ICU setting remains debated. This study compared the complication rates of anatomical landmark-guided versus ultrasound-guided CVC insertion in ICU patients. Methods: A prospective cohort study was conducted in the ICU of a tertiary care hospital. Patients requiring CVC were divided into two groups: anatomical landmark-guided and ultrasound-guided insertion. The primary outcome was the incidence of complications, including arterial puncture, hematoma, and pneumothorax. Secondary outcomes included cannulation time and the number of cannulation attempts. Results: A total of 39 patients were included in the study. The incidence of complications was significantly lower in the ultrasound-guided group (2 complications) compared to the anatomical landmark group (7 complications) (p=0.017). The most common complication was arterial puncture, occurring in 7 patients in the anatomical landmark group and 2 patients in the ultrasound-guided group. Conclusion: Ultrasound guidance significantly reduces the risk of complications during CVC insertion in the ICU. This technique should be considered the standard of care for CVC insertion in this setting.